Implementasi Program Penguatan Pendidikan Karakter (Ppk) Dalam Pembelajaran Pendidikan Agama Islam - Lubis, Rahmat Rifai (Al-Fikru: Jurnal Ilmiah, 2019)
The Character Building Strengthening Program, hereinafter abbreviated as PPK, is an educational movement under the responsibility of the education unit to strengthen the character of students through the harmonization of the process of heart, taste, thought, and sports by involving and cooperating between education units, families, and the community as part of the National Mental Revolution Movement (GNRM). In the implementation of the program of character education strengthening carried out in three ways namely Intra-Curricular, co-curricular, Extracurricular. In the intraarticular scope of course through the material of Islamic religious education itself, in that material there are spiritual values that basically teach the goodness to students. of course in this case in line with the program of strengthening the character education itself. In extra-curricular activities, such as Pesantren Kilat, Da'wah institutions, fostering Islamic talent and so on.